"Self‐Peel‐Off" Transfer Produces Ultrathin Polyvinylidene‐Fluoride‐Based Flexible Nanodevices. Issue 4 (23rd February 2017) - Tai, Yanlong; Lubineau, Gilles
Abstract : Here, a new strategy, self‐peel‐off transfer, for the preparation of ultrathin flexible nanodevices made from polyvinylidene‐fluoride (PVDF) is reported. In this process, a functional pattern of nanoparticles is transferred via peeling from a temporary substrate to the final PVDF film. This peeling process takes advantage of the differences in the work of adhesion between the various layers (the PVDF layer, the nanoparticle‐pattern layer and the substrate layer) and of the high stresses generated by the differential thermal expansion of the layers. The work of adhesion is mainly guided by the basic physical/chemical properties of these layers and is highly sensitive to variations in temperature and moisture in the environment. The peeling technique is tested on a variety of PVDF‐based functional films using gold/palladium nanoparticles, carbon nanotubes, graphene oxide, and lithium iron phosphate. Several PVDF‐based flexible nanodevices are prepared, including a single‐sided wireless flexible humidity sensor in which PVDF is used as the substrate and a double‐sided flexible capacitor in which PVDF is used as the ferroelectric layer and the carrier layer. Results show that the nanodevices perform with high repeatability and stability. Self‐peel‐off transfer is a viable preparation strategy for the design and fabrication of flexible, ultrathin, and light‐weight nanodevices. Abstract : Mechanism of the "self‐peel‐off" transfer (SPOT) technique via the temperature‐ and humidity‐sensitive properties of both polyvinylidene‐fluoride (PVDF) and nanomaterials. SPOT is a promising strategy to fabricate flexible, ultrathin, and light‐weighted PVDF‐based nanodevices.